Interactions of Feelings of Competence and Motivation of Pre-Service Science Teachers in Their Laboratory Course: A Dynamic Multilevel Modeling Approach - Smit, Robbert; Rietz, Florian; Robin, Nicolas (Frontiers in Education, 2021)
Dynamic structural equation modeling was applied to examine feelings of competence and in the moment motivation among pre-service science teachers (N = 101) enrolled in a course on practical biology during their second semester. The student teachers completed a short questionnaire 18 times, and the interaction between their feelings of competence and momentary motivation over time was examined in relation to control-value theory. The autoregressive values of both variables were significant, and a pattern was observed of low competence at the beginning of the course session, combined with low motivation in the moment. Feelings of competence increased by the end of each course session but returned to a low level at the beginning of the next session. Momentary motivation followed this back-and-forth shifting somewhat but showed more carryover effects. The student teachers’ motivation depended on their feelings of competence from the previous moment in the biology course session, but feelings of competence did not depend on their motivation.